Corrigendum to: INTELLECTUAL RELIGIOSITY OF ISLAMIC BOARDING SCHOOL IN A. MUSTOFA BISRI’S POETRY [15(2), (2017), 324-344] - Suwito NS (IBDA` : Jurnal Kajian Islam dan Budaya, 2017)
Corrigendum to: Based on the error submitted by the author of the article to the editors on July 19, 2018, that the author of the article is only one author and written Abdul Wachid BS, this article should consist of four authors namely Abdul Wachid BS, Herman J. Waluyo, Rachmat Djoko Pradopo, and Suyitno. so this correction is made to make checks for the readers.